Two Waves of COVID-19 in University Setting: Mental Health and Underlying Risk Factors - Křeménková, Lucie; Novotný, Jan Sebastian; Kvintová, Jana (Frontiers in Psychology, 2021)
The aim of the paper was to assess the differences in the mental distress of university students in the first and second waves of Covid-19, to compare these levels with that of the general population as well as to identify the risk factors associated with the changes in mental health. A total of 2025 university students in core psychology courses in all years of study at the Faculty of Education at Palacký University Olomouc were approached via e-mail. Of this number of students, 800 students took part in the study, divided into two groups from the spring (N=438) and autumn (N=362) pandemic waves. The data were collected online via Google Forms using a battery of questionnaires and analyzed using the Wilcoxon–Mann–Whitney test, One-Sample Wilcoxon Signed Rank Test and binary logistic regression. The results showed a high prevalence of depressive symptoms (38.4% and 51.4%), significant anxiety (43.8% and 37%) and high stress (19.9% and 22.9%) among students in both waves of the pandemic. Depression and stress also increased significantly during the second wave compared with the first one (r=0.18 [0.12, 0.25] and r=0.08 [0.01, 0.14]). Finally, university students showed significantly higher levels of mental distress than the general population in all of the variables and in both waves (r=0.42 to 0.86). A variety of factors influenced different aspects of mental distress in the spring and autumn pandemic waves. Emotion regulation emerged as the most significant and pervasive factor, both influencing all of the three indicators of mental distress and being a significant predictor in both waves.